2013
DOI: 10.1161/circimaging.113.000936
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Strain in Pulmonary Hypertension

Abstract: Since 2009, there have been ≥170 articles published in the cardiopulmonary literature on right ventricular (RV) echocardiographic strain imaging, including several in Circulation: Cardiovascular Imaging. Of particular interest has been the effort to use RV echocardiographic strain imaging to assess RV systolic function in pulmonary hypertension and the relationship of RV strain to disease severity and outcomes. In this issue of Circulation: Cardiovascular Imaging, Fine et al, 1 from the Mayo Clinic echo group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…[43][44][45] CI is largely controlled by venous return, which is determined by the difference between mean systemic venous pressure and RAP. Several authors 45,46 have suggested that RAP is a dependent variable, whereas venous return an independent variable because RAP decreased when cardiac output increases.…”
Section: Downloaded From Predictors Of Outcome In Pulmonary Hypertensionmentioning
confidence: 99%
“…[43][44][45] CI is largely controlled by venous return, which is determined by the difference between mean systemic venous pressure and RAP. Several authors 45,46 have suggested that RAP is a dependent variable, whereas venous return an independent variable because RAP decreased when cardiac output increases.…”
Section: Downloaded From Predictors Of Outcome In Pulmonary Hypertensionmentioning
confidence: 99%
“…In a recent editorial, Reichek 55 noted that there have been several hundred publications on RV myocardial imaging over the past few years. Considering this impressive body of literature, an obvious question is, How does myocardial deformation imaging affect screening or prediction of outcome in patients with PH?…”
Section: Myocardial Deformation Imaging Of the Rv: Holy Grail Or Flavmentioning
confidence: 99%
“…Looking at the movement of one side of the tricuspid annulus and measuring DTI from this region may not be as valuable once RV strain and 3D RVEF become more advanced and adopted. 61 However, many echocardiographic laboratories are currently using the conventional measures along with the newer methods described below for complete RV echocardiographic analysis. 62 …”
Section: Future Directions Of Rv Assessmentmentioning
confidence: 99%
“…64 The normal and abnormal values still vary, depending on the vendor providing the strain software, which makes comparison between centers very difficult. 61 Worsening of RV longitudinal strain has been associated with increased pulmonary artery pressures, decreased TAPSE, worsened functional class, and increased mortality from PAH (Fig. 6).…”
Section: Rv Strainmentioning
confidence: 99%